Consumer Insights on the Presence of Acrylamide in Baked Products: Perception, Awareness and Behaviour - Alija, Durim; Nikolovska Nedelkoska, Daniela; Olędzki, Remigiusz; Harasym, Joanna (Opinia konsumencka na temat obecności akrylamidu w produktach piekarniczych: postrzeganie, świadomość i zachowania, 2024)
Aim: This study examined consumer awareness, attitudes, and purchasing habits regarding the pre-sence of acrylamide in bakery products, with a focus on understanding the level of knowledge and concern about this chemical in food. Methodology: A survey was conducted among 327 respondents, with 70.34% identifying as women and 29.66% as men. The majority were young adults aged 18 to 24, and 79.82% were from the Republic of North Macedonia. Results: Over half of the respondents (50.76%) were unaware of the presence of acrylamide in food products, and 30.3% were introduced to the topic through social media platforms. Most participants reported regularly purchasing bakery products, with bread being the most frequently bought item. A significant proportion (68.6%) purchased these products from supermarkets. While 33.03% of respondents expressed concern about acrylamide, 52.29% believed it could pose a health risk, and 42.51% were unsure. Trust in health organizations' information was generally high. Taste and ingredient quality were identified as the most important factors influencing product choices. A large majority (68.2%) considered the nutritional content of bakery products important, and 88.69% preferred products made with natural ingredients. Furthermore, 43.37% of the respondents actively avoided certain bakery products, and 20.18% specifically sought products with lower acrylamide content. Implications and recommendations: The findings highlight a clear demand for more information about acrylamide, with many respondents expecting support from national health authorities. This suggests a pressing need for increased public awareness and educational initiatives to address consumer concerns about acrylamide in food and its potential health risks. Most respondents expressed the need to obtain health information on acrylamide and expect support from state health agencies, which indicates the need to increase public awareness and education in this regarding acrylamide exposure and risks.
Nauki Inżynierskie i Technologie = Engineering Sciences and Technologies, 2024, Nr 40, s. 1-17